Numerical Research about Influence of Blade Outlet Angle on Flow-Induced Noise and Vibration for Centrifugal Pump. (9th March 2014) - Yang, Ailing; Lang, Dapeng; Li, Guoping; Chen, Eryun; Dai, Ren
Abstract : A hybrid numerical method was used to calculate the flow-induced noise and vibration of the centrifugal pump in the paper. The unsteady flows inside the centrifugal pumps with different blade outlet angles were simulated firstly. The unsteady pressure on the inner surface of the volute and the unsteady force applied on the impeller were analyzed. Then the vibration of the volute and sound field were calculated based on an acoustic-vibro-coupling method. The results show that the pump head has increased 7% while the hydraulic efficiency decreased 11.75% as blade outlet angles increased from 18° to 39°. The amplitude of pressure fluctuation at the first blade passing frequency has decreased but increased at the second-order blade passing frequency as the angle growing. The total fluctuation power near volute tongue goes up about 12% every 3° increment of blade outlet angle. The results also show that vibrating-velocity of the volute at second-order blade passing frequency is much higher than at other frequencies, and the velocity increases rapidly as blade outlet angle varies from 18° to 39°. At the same time, the sound pressure level outside the pump has increased about 8.6 dB when the angle increased from 18° to 39°.